PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN POLITEKNIK MUARA TEWEH KABUPATEN BARITO UTARA PROVINSI KALIMANTAN TENGAH - Maslianor, Maslianor; Sulastini, Sulastini; Maskur, Maskur (Manajemen: Jurnal Ekonomi, 2025)
This research was conducted with the aim of: (1).Testing and Analyzing the Effect of Partial Competence on the Performance of Muara Teweh Polytechnic Employees. (2). Testing and analyzing the partial influence of work discipline on the performance of Muara Teweh Polytechnic employees.  and (3).Testing and Analyzing the Effect of Competency and Work Discipline Simultaneously on the Performance of Muara Teweh Polytechnic Employees. This research uses explanatory research. Whereas Data sources use primary data through questionnaires and secondary data. The population in this research are individual employees who are still actively working at Muara Teweh Polytechnic. The sample in this research was all employees of the Muara Teweh Polytechnic, North Barito Regency, Central Kalimantan Province, totaling 40 people with a sampling technique using Saturated Sampling.  Data collection techniques using observation, questionnaires, literature and documents. Data validity testing is carried out using Validation Tests and Reliability Tests.  The data analysis technique uses the IBM SPSS Statistics Version 25 program. The analysis method used is multiple linear regression analysis